Understanding daily life in political and scientific historical sources by a taxonomic view (TEL Tempo, Espaço e Linguagem, 2021)
The objective of this article is to analyze unconventional historic sources to daily history studies. Based on José de Assunção Barros’ works, I will show how some sources commonly faced to science history and political history might reveal important proprieties that bind them with daily history, developing scientific analyses.